Replication-Competent Oropouche Virus in Semen of Traveler Returning to Italy from Cuba, 2024 - Concetta Castilletti; Ralph Huits; Rebeca Passarelli Mantovani; Silvia Accordini; Francesca Alladio; Federico Gobbi (Emerging Infectious Diseases)
A febrile man in Italy who had traveled to Cuba in July 2024 was diagnosed with Oropouche fever. Reverse transcription PCR detected prolonged shedding of Oropouche virus RNA in whole blood, serum, urine, and semen. Sixteen days after symptom onset, replication-competent virus was detected in semen, suggesting risk for sexual transmission.